BILATERAL ACUTE PERIPHERAL FACIAL NERVE DAMAGE – CASE REPORT - Neja Turk Hojs; Tanja Loboda (Slovenska pediatrija)

(untitled)
The paper presents an overview of the theoretical bases of the peripheral facial nerve palsy; possible causes, assessment of the degree of damage, diagnostics and treatment options. The clinical case presents a girl with peripheral palsy pathology who was treated at the Department for Child, Adolescent and Developmental Neurology at the University Medical Centre Ljubljana.